2013
DOI: 10.1111/j.1600-0706.2013.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence and phylogenetic distance in communities of mammalian ectoparasites: limiting similarity versus environmental filtering

Abstract: Similarity between species plays a key role in the processes governing community assembly. The co‐occurrence of highly similar species may be unlikely if their similar needs lead to intense competition (limiting similarity). On the other hand, persistence in a particular habitat may require certain traits, such that communities end up consisting of species sharing the same traits (environmental filtering). Relatively little information exists on the relative importance of these processes in structuring parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 93 publications
2
36
0
2
Order By: Relevance
“…This result suggests that competition between related consumers is not a major driver of phylogenetic signal asymmetry at this scale. A recent study on the correlation between phylogenetic distance and individual level co‐occurrence in flea communities (Krasnov et al ) also demonstrated significant co‐occurrence of pairs of closely related fleas, which indicates a prevalence of environmental, or host, filtering in determining the composition of flea assemblages on individual hosts. The parasitic lifestyle of endophagous insects also imposes numerous restrictions on host use that probably increase the influence of those kinds of filters.…”
Section: Discussionmentioning
confidence: 92%
“…This result suggests that competition between related consumers is not a major driver of phylogenetic signal asymmetry at this scale. A recent study on the correlation between phylogenetic distance and individual level co‐occurrence in flea communities (Krasnov et al ) also demonstrated significant co‐occurrence of pairs of closely related fleas, which indicates a prevalence of environmental, or host, filtering in determining the composition of flea assemblages on individual hosts. The parasitic lifestyle of endophagous insects also imposes numerous restrictions on host use that probably increase the influence of those kinds of filters.…”
Section: Discussionmentioning
confidence: 92%
“…The infracommunities recorded in PNSI and RVSMJ are composed 100 and 96.6 %, respectively, of species of parasites of different genres. This fact, according to Ingram and Shurin (2009) and Krasnov et al (2014), corresponds to the association of some species closely related parasites, thus reducing competition among them by the host. The specificity of the parasites in Sergipe was low (56 %) compared with studies by Dick and Gettinger (2005), Dick (2007), Dos Santos et al (2013), and Vasconcelos et al (2016).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, these environmental filters represent an interplay between filtering through the abiotic environment and filtering through host composition. In other words, abiotic conditions and host composition in a region or a locality act as filters to restrict co‐occurring flea species to a certain subset sharing traits (on both continental and regional scale) and phylogenetic affinity (on the continental scale) (Tofts and Silvertown , Statzner et al ; see Krasnov et al for fleas). The relative importance of these two components of environmental filtering appears to differ across scales.…”
Section: Discussionmentioning
confidence: 99%